Black Carbon aerosol characteristics and radiative forcing over the high altitude glacier region of Himalaya-Karakorum-Hindukush. (1st October 2020) - Zeb, Bahadar; Alam, Khan; Nasir, Jawad; Mansha, Muhammad; Ahmad, Ifthikhar; Bibi, Samina; Malik, Sher Muhammad; Ali, Mushtaq
Abstract: Absorbing aerosols mainly Black Carbon (BC) have potential effects on the hydrological cycle and climate change over the high-altitude regions particularly in South Asia. The BC measurements are sparse in high altitude locations of the world particularly over the Northern regions of Pakistan. This study investigated the diurnal/monthly variations of BC and its climatic impacts during the period of 2016–2017 over four high altitude locations, i.e., Astore, Gilgit, Sost and Skardu located in the Himalaya-Karakorum-Hindukush (HKH) mountain ranges in Northern Pakistan. The Optical Properties of Aerosols and Clouds (OPAC) model was used for the estimation of aerosol optical properties, e.g., Aerosol Optical Depth (AOD), Asymmetry Parameter (AP) and Single Scattering Albedo (SSA) using the BC number density corresponding to the BC mass concentration. Then the model derived optical properties (AOD, AP and SSA), surface reflectance, ozone and water vapor were used in Santa Barbara DISORT Atmospheric Radiative Transfer (SBDART) model for the calculation of BC aerosol radiative forcing (ARF) at the Top Of Atmosphere (TOA), Surface (SUR) and within the ATMosphere (ATM). The results revealed that the mean monthly BC concentrations were maximum during November (3.05 ± 0.7 μg/m 3 ) as well as in December (3.05 ± 0.5 μg/m 3 ) at Gilgit and minimum during August (1.1 ± 0.3 μg/m 3 ) at Sost. Correspondingly, the diurnal variation of BC concentrations displayed strong fluctuations, with high concentrations in the late night and early morning during November and December for Astore and Gilgit, respectively. Generally, the BC concentrations were maximum/minimum in the morning/evening during May, June, August and September at all locations. The correlation of BC with different meteorological parameters showed that the BC has positive correlation with temperature and wind speed, while negative with relative humidity and rainfall. The HYSPLIT back trajectory analysis revealed that air masses arrived the study locations from both long distance (Turkmenistan, Tajikistan, Uzbekistan, Iran, Afghanistan, India, and China) and local sources. The monthly mean maximum and minimum BC ARF values at SUR (TOA) were found to be −43.7 ± 3.0 W/m 2 (−8.2 ± 0.2 W/m 2 ) and −16.4 ± 1.0 W/m 2 (−1.2 ± 0.1 W/m 2 ), respectively, giving an averaged atmospheric forcing of 35.7 ± 2.3 W/m 2 and 15.2 ± 1.9 W/m 2 . Highlights: The diurnal/monthly variations of BC were analyzed in the least study region of HKH. Contrasting variation in BC was observed in daytime and nighttime at all locations. The micro-meteorological parameters have significant influence on the BC variation. Higher AOD and lower SSA and AP values were reported in winter months. The large differences between TOA and SRF forcing produce warming effect within ATM.